Comportamiento agronómico del cultivo de arroz a la aplicación de fertilizantes nitro azufrados más encapsuladores orgánicos en la zona de Babahoyo - Mora Medina, Byron (2013)
Rice (Oryza sativa L) is the most important cereal in the market, being consumed as a staple food for more than 50% of the world population. One of the most important products in the country and the main power supply, currently about 415.000 have it planted a year under rainfed conditions (rainfall) and irrigation; with an average productivity of 3.9 ton / ha of rice shell, which is considered low compared to other countries that get 6-7 t / ha. The biggest area of planting this grass is in the provinces of Guayas and Los Rios with about 92 % of the total production of the country. Under rainfed conditions are planted 32% and 60% under irrigation. The objective of this research was to determine the behavior of rice to fertilizer application nitro - sulfur mixed with organic Wrappers, to evaluate their effect on performance. The work was done on the the farm “La Ventura”, owned by Mr. Roberto Guayaquil, located at km 4 Babahoyo via cocoa -Mata. Rice variety lNlAP -17, with 11 treatments in plots of 30 m2, which were distributed in a completely randomized design blocks was investigated. For the evaluation of the average Tukey test at 5% significance was used. At the end of the crop cycle were evaluated: plant height, number of tillers, grains per panicle, panicle length and number, days to flowering, days to harvest, 1.000 seeds weight, yield per hectare. and an economic analysis of the treatments.